IMPLEMENTASI PEMBELAJARAN AKTIF KREATIF EFEKTIF DAN MENYENANGKAN (PAKEM) UNTUK PENDIDIKAN SAINS DI SEKOLAH - Zuhdi Ma'aruf (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2009)
The importance of applying various approaches and strategies in learning science in schools is a matterwhich should be the concern of educators. Because the process of learning good science done in theclassroom teachers will produce good quality science learning for students are learners. Indication of a goodquality of learning is when students learn in active creative and not boring. This writing will discuss how toimplement an effective strategy of active learning creative and fun that can be used by teachers in schools.